How Food Insecurity and Financial Difficulty Relate to Emotional Well-Being and Social Functioning. Issue 1 (January 2022) - Kamimura, Akiko; Higham, Rebecca; Panahi, Samin; Lee, Edward; Griffin, Rachel J.; Sundrud, Justine; Lucero, Mary
Abstract: Objectives: Medically uninsured individuals living in poverty experience poor health and face social barriers that negatively affect their health. The purpose of this study was to examine the association between social barriers, particularly healthy food availability and financial difficulty, and well-being among uninsured free clinic patients in the United States. Methods: Data were collected using a self-administered paper survey at a free clinic from adult patients who spoke and read English or Spanish (N = 666) from January to April 2019. Results: Better neighborhood healthy food availability is associated with better self-reported general health. Food security is related to better emotional well-being and social functioning. Having difficulty paying rent or a mortgage is linked to worse emotional well-being and social functioning. Conclusions: Providing health education programs may not be sufficient to promote healthy eating among underserved populations because of the social barriers that they experience, such as food insecurity and financial difficulty. Future research could be performed to determine how these social factors influence those of different social and cultural backgrounds than the participants in this study. Abstract : Uninsured individuals living in poverty experience poor health and face social barriers that negatively affect their health. This article examines the association between social barriers, particularly healthy food availability and financial difficulty, and well-being among uninsured free clinic patients in the United States and helps develop effective health-promotion programs for underserved populations.